Artificial Intelligence, Data Sensors and Interconnectivity: Future Opportunities for Heart Failure - Patrik Bachtiger; Carla M Plymen; Punam A Pabari; James P Howard; Zachary I Whinnett; Felicia Opoku; Stephen Janering; Aldo A Faisal; Darrel P Francis; Nicholas S Peters (Cardiac Failure Review)
A higher proportion of patients with heart failure have benefitted from a wide and expanding variety of sensor-enabled implantable devices than any other patient group. These patients can now also take advantage of the ever-increasing availability and affordability of consumer electronics. Wearable, on- and near-body sensor technologies, much like implantable devices, generate massive amounts of data. The connectivity of all these devices has created opportunities for pooling data from multiple sensors – so-called interconnectivity – and for artificial intelligence to provide new diagnostic, triage, risk-stratification and disease management insights for the delivery of better, more personalised and cost-effective healthcare. Artificial intelligence is also bringing important and previously inaccessible insights from our conventional cardiac investigations. The aim of this article is to review the convergence of artificial intelligence, sensor technologies and interconnectivity and the way in which this combination is set to change the care of patients with heart failure.